2004
DOI: 10.1097/01.gme.0000087981.28957.cf
|View full text |Cite
|
Sign up to set email alerts
|

Transition from estrogen therapy to raloxifene in postmenopausal women: effects on treatment satisfaction and the endometrium—a pilot study

Abstract: Gradual conversion to raloxifene from low-dose estrogen, with a progression from 60 mg every alternate day to 60 mg/day, is a viable option in potentially symptomatic, postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 19 publications
4
20
0
Order By: Relevance
“…Women taking transdermal 17A-estradiol 25 Kg/day with RLX had lower vasomotor symptoms scores than women taking RLX alone, 17 similar to what occured with oral 17A-estradiol in this study, demonstrating that either administration regimen can produce systemic effects. Serum estrogen levels attained with exogenous estrogen therapy depend on a combination of dose, formulation (micronized 17A-estradiol or conjugated equine estrogens), and route of administration.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Women taking transdermal 17A-estradiol 25 Kg/day with RLX had lower vasomotor symptoms scores than women taking RLX alone, 17 similar to what occured with oral 17A-estradiol in this study, demonstrating that either administration regimen can produce systemic effects. Serum estrogen levels attained with exogenous estrogen therapy depend on a combination of dose, formulation (micronized 17A-estradiol or conjugated equine estrogens), and route of administration.…”
Section: Discussionsupporting
confidence: 89%
“…12 Endometrial thickness was significantly greater when transdermal estrogen (25 Kg/day) was given concomitantly with RLX than with RLX alone. 17 We cannot compare the current results with those seen in previous estrogen studies 20 because this study had no estrogen-only arm, baseline assessments were based on TVU and did not include an endometrial biopsy, and only two women had endometrial hyperplasia. Thus, we cannot draw a definitive conclusion about any effects of RLX on preventing histological changes in the endometrium in a manner similar to that of progestin when administered in combination with estrogen.…”
Section: Discussionmentioning
confidence: 87%
“…An appropriate TSEC would alleviate hot flushes, treat vulvar and vaginal atrophy, and protect against postmenopausal bone loss without stimulating the endometrium or the breast. Importantly, not all estrogen-SERM combinations will be effective; for example, endometrial stimulation was reported with estradiol-raloxifene combinations (4,5).…”
mentioning
confidence: 95%
“…Moreover, clinical trials evaluating the effects of RLX in combination with estrogen on menopausal symptoms have shown evidence of endometrial stimulation. [40][41][42] These findings indicate that RLX, unlike BZA, does not adequately protect the endometrium from estrogen stimulation and that the neutral effects observed for BZA/CE on the reproductive tract may not apply to other SERM/estrogen combinations. Thus, the future development of other TSECs must involve thorough evaluation of efficacy and safety to ensure protection of the endometrium and breast.…”
Section: Discussionmentioning
confidence: 82%